GmABCG5, an ATP-binding cassette G transporter gene, is involved in the iron deficiency response in soybean - Wang, Yu; Zhang, Xuemeng; Yan, Yuhan; Niu, Tingting; Zhang, Miao; Fan, Chao; Liang, Wenwei; Shu, Yongjun; Guo, Changhong; Guo, Donglin; Bi, Yingdong (Frontiers in Plant Science, 2024)
Iron deficiency is a major nutritional problem causing iron deficiency chlorosis (IDC) and yield reduction in soybean, one of the most important crops. The ATP-binding cassette G subfamily plays a crucial role in substance transportation in plants. In this study, we cloned the GmABCG5 gene from soybean and verified its role in Fe homeostasis. Analysis showed that GmABCG5 belongs to the ABCG subfamily and is subcellularly localized at the cell membrane. From high to low, GmABCG5 expression was found in the stem, root, and leaf of young soybean seedlings, and the order of expression was flower, pod, seed stem, root, and leaf in mature soybean plants. The GUS assay and qRT-PCR results showed that the GmABCG5 expression was significantly induced by iron deficiency in the leaf. We obtained the GmABCG5 overexpressed and inhibitory expressed soybean hairy root complexes. Overexpression of GmABCG5 promoted, and inhibition of GmABCG5 retarded the growth of soybean hairy roots, independent of nutrient iron conditions, confirming the growth-promotion function of GmABCG5. Iron deficiency has a negative effect on the growth of soybean complexes, which was more obvious in the GmABCG5 inhibition complexes. The chlorophyll content was increased in the GmABCG5 overexpression complexes and decreased in the GmABCG5 inhibition complexes. Iron deficiency treatment widened the gap in the chlorophyll contents. FCR activity was induced by iron deficiency and showed an extraordinary increase in the GmABCG5 overexpression complexes, accompanied by the greatest Fe accumulation. Antioxidant capacity was enhanced when GmABCG5 was overexpressed and reduced when GmABCG5 was inhibited under iron deficiency. These results showed that the response mechanism to iron deficiency is more actively mobilized in GmABCG5 overexpression seedlings. Our results indicated that GmABCG5 could improve the plant’s tolerance to iron deficiency, suggesting that GmABCG5 might have the function of Fe mobilization, redistribution, and/or secretion of Fe substances in plants. The findings provide new insights into the ABCG subfamily genes in the regulation of iron homeostasis in plants.